Management of Adult Patients with Primary Immune Thrombocytopenia (ITP) in Clinical Practice: A Consensus Approach of the Spanish ITP Expert Group. (22nd August 2019) - Mingot-Castellano, M. Eva; Román, M. Teresa Álvarez; Fernández Fuertes, Luis Fernando; González-López, Tomás José; Guinea de Castro, José María; Jarque, Isidro; López-Fernández, M. Fernanda; Lozano, Maria Luisa; Sánchez González, Blanca; Ferreiras, David Valcárcel; González Porras, José Ramón
Abstract : Background and Objective . Diagnosis and management of primary immune thrombocytopenia (ITP) have changed dramatically in the last decade. The aim of the study was to obtain information about the opinion of the Spanish ITP Group (GEPTI) members regarding the best clinical practices for diagnosis and management of adult patients with ITP. Materials and Methods . A two-round Delphi method was carried out by sending to 129 experts a 90-item questionnaire developed by 11 specialists, with a 4-point Likert scale ("never, " "sometimes, " "frequently, " and "always") for the assessment of responses. Results . Forty out of the 129 experts participated in the survey (participation rate 30.2%) and 39 completed the questionnaire (response rate 97.5%). Salient consensus points included the following: the need to indicate workup studies from a sustained platelet count < 100 x 10 9 /L in the absence of a clear etiology; bone marrow aspiration in elderly patients with suspected ITP; beginning treatment in asymptomatic patients with a platelet count < 20 x 10 9 /L; not exceeding 6-7 weeks of corticosteroid therapy; switching from corticosteroids to one thrombopoietin receptor agonist (TRA); switching to other TRA or other options as combinations of them with immunosuppressive drugs in case of failure; how to reduce tapering TRA; treating patients with symptomatic persistent ITP and platelet count > 20 x 10 9 /L; and considering mucosal or severe bleeding as a basic criterion for hospital admission. Conclusions . The present consensus document provides a reference framework for the management of patients with ITP in clinical practice.